2019
DOI: 10.1016/j.yebeh.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evolving dynamic networks: An underlying mechanism of drug resistance in epilepsy?

Abstract: At least one-third of all people with epilepsy have seizures that remain poorly controlled despite an increasing number of available anti-epileptic drugs (AEDs). Often, there is an initial good response to a newly introduced AED, which may last up to months, eventually followed by the return of seizures thought to be due to the development of tolerance. We introduce a framework within which the interplay between AED response and brain networks can be explored to understand the development of tolerance. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Mechanisms of action of AEDs are well characterized at a cellular level, but how those relate to antiseizure effects is incompletely understood. Our results support the notion of a common pathway of AED effects, arising through a large‐scale network effect 47 . Studies in other epilepsy cohorts have reported changes in global efficiency (the inverse of L) with topiramate but not with lamotrigine, levetiracetam, or valproate 48 .…”
Section: Discussionsupporting
confidence: 88%
“…Mechanisms of action of AEDs are well characterized at a cellular level, but how those relate to antiseizure effects is incompletely understood. Our results support the notion of a common pathway of AED effects, arising through a large‐scale network effect 47 . Studies in other epilepsy cohorts have reported changes in global efficiency (the inverse of L) with topiramate but not with lamotrigine, levetiracetam, or valproate 48 .…”
Section: Discussionsupporting
confidence: 88%
“…To investigate the impact of sleep and CORT on the ED likelihood during the day, we employed a phenomenological mathematical model to simulate brain excitability when perturbed by those external forces. Unlike in previous works where the variation of the brain excitability was constant [48] or perturbed by a fixed constant [49], this model describes cortical excitability as a dynamical variable that is modulated by dynamic external factors, such as sleep or CORT. We used sleep stages and CORT levels collected from healthy subjects to inform the dynamics of the variable representing the status of brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…The model used in this study is based on the normal form of a subcritical Hopf bifurcation [48, 49, 57], whose co-existing states reflect two distinct types of neural activity. The first is a background state, represented by a steady-state solution in the model, whilst the second is an epileptiform state, represented by a high-amplitude oscillation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When dealing with crucial issues in epilepsy, such as symptomatic diagnosis, seizure onset zone (SOZ) localization, presurgical evaluation, prognosis of medication responses, etc. [5][6][7][8][9] most neurologists make comprehensive decisions based on multifaceted clinical information. In that process, medical techniques such as functional magnetic resonance imaging (fMRI) and intracranial electroencephalogram (EEG) recordings certainly help a lot, however, artificial efforts are still paid to analyze.…”
Section: Introductionmentioning
confidence: 99%